Catalonia Suicide Risk Code Epidemiology (CSRC-Epi) study: protocol for a population-representative nested case–control study of suicide attempts in Catalonia, Spain. Issue 7 (12th July 2020) - Mortier, Philippe; Vilagut, Gemma; Puértolas Gracia, Beatriz; De Inés Trujillo, Ana; Alayo Bueno, Itxaso; Ballester Coma, Laura; Blasco Cubedo, María Jesús; Cardoner, Narcís; Colls, Cristina; Elices, Matilde; Garcia-Altes, Anna; Gené Badia, Manel; et al.
Abstract : Introduction: Suicide attempts represent an important public health burden. Centralised electronic health record (EHR) systems have high potential to provide suicide attempt surveillance, to inform public health action aimed at reducing risk for suicide attempt in the population, and to provide data-driven clinical decision support for suicide risk assessment across healthcare settings. To exploit this potential, we designed the Catalonia Suicide Risk Code Epidemiology (CSRC-Epi) study. Using centralised EHR data from the entire public healthcare system of Catalonia, Spain, the CSRC-Epi study aims to estimate reliable suicide attempt incidence rates, identify suicide attempt risk factors and develop validated suicide attempt risk prediction tools. Methods and analysis: The CSRC-Epi study is registry-based study, specifically, a two-stage exposure-enriched nested case–control study of suicide attempts during the period 2014–2019 in Catalonia, Spain. The primary study outcome consists of first and repeat attempts during the observation period. Cases will come from a case register linked to a suicide attempt surveillance programme, which offers in-depth psychiatric evaluations to all Catalan residents who present to clinical care with any suspected risk for suicide. Predictor variables will come from centralised EHR systems representing all relevant healthcare settings. The study's sampling frame will be constructed using population-representative administrative lists of Catalan residents. Inverse probability weights will restore representativeness of the original population. Analysis will include the calculation of age-standardised and sex-standardised suicide attempt incidence rates. Logistic regression will identify suicide attempt risk factors on the individual level (ie, relative risk) and the population level (ie, population attributable risk proportions). Machine learning techniques will be used to develop suicide attempt risk prediction tools. Ethics and dissemination: This protocol is approved by the Parc de Salut Mar Clinical Research Ethics Committee (2017/7431/I). Dissemination will include peer-reviewed scientific publications, scientific reports for hospital and government authorities, and updated clinical guidelines. Trial registration number: NCT04235127 .